2019
DOI: 10.1136/bmjopen-2018-023003
|View full text |Cite
|
Sign up to set email alerts
|

Association between homocysteine, vitamin B12, folic acid and erectile dysfunction: a cross-sectional study in China

Abstract: ObjectivesErectile dysfunction (ED) affects up to 53.4% of men aged 30–80 years. In this study, we aimed to examine the association between homocysteine (HCY), vitamin B12 (B12), folic acid (FA) and ED.DesignCross-sectional study.SettingGuangxi, China.ParticipantsA total of 1381 participants who completed questionnaires were included, between September 2009 and December 2009.MeasuresED was evaluated by the International Index of Erectile Function scores. Also, the values of HCY, B12 and FA were acquired. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
1
23
3
Order By: Relevance
“…According to the established retrieval formula, we searched a total of 1,341 related studies, deleted duplicates and made preliminary screening according to titles and abstracts, and the remaining 21 literatures entered the full‐text reading stage. After reading through the full text of 21 articles, a total of six studies (Attia et al., 2019; Chen et al., 2019; Gupta et al., 2020; Karabakan et al., 2016; Sansone et al., 2018; Yan et al., 2014) including 1,842 participants were finally included in our meta‐analysis. Among the six studies, five are case–control studies and one is cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the established retrieval formula, we searched a total of 1,341 related studies, deleted duplicates and made preliminary screening according to titles and abstracts, and the remaining 21 literatures entered the full‐text reading stage. After reading through the full text of 21 articles, a total of six studies (Attia et al., 2019; Chen et al., 2019; Gupta et al., 2020; Karabakan et al., 2016; Sansone et al., 2018; Yan et al., 2014) including 1,842 participants were finally included in our meta‐analysis. Among the six studies, five are case–control studies and one is cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reporting the FA levels in the ED group and non‐ED group were included in the meta‐analysis(Attia et al., 2019; Chen et al., 2019; Gupta et al., 2020; Karabakan et al., 2016; Sansone et al., 2018; Yan et al., 2014). The pooled MD revealed that individuals without ED had about 3.37 ng/ml higher of FA levels than those with ED (MD = 3.37, 95% CI 1.49–5.52, p = 0.004), with severe heterogeneity existed ( I 2 = 86%) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large study, Hcys, FA and B12 levels were recently assessed on a total of 1381 patients (688 ED and 693 non-ED). The authors reported a significant association between Hcys and erectile function, especially in older men (age ≥ 60), with a larger proportion of HHcys in the ED group than the non-ED group (43.02% versus 37.52%, p = 0.037) [ 21 ]. In particular, Demir et al demonstrated that HHcys increases more than three times the risk of ED [ 22 ].…”
Section: Hyperhomocysteinemia and Erectile Dysfunction: Clinical Ementioning
confidence: 99%
“…It has been hypothesized that FA deficiency could play a central role in ED development both by directly interfering with the NO metabolism and by favoring the development of HHcys. Some authors [ 3 , 28 , 29 , 30 ] consider low serum FA levels as a risk factor for ED whereas others do not agree [ 21 ]. Sansone et al reported significant lower serum FA levels and higher serum Hcys levels in ED patients compared to non-ED patients, even if, surprisingly, these authors did not find a significant correlation between Hcys and FA levels [ 28 ].…”
Section: Hyperhomocysteinemia and Erectile Dysfunction: Clinical Ementioning
confidence: 99%